(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The objective of this experimental work is to develop and validate a reverse phase high performance liquid chromatographic (RP-HPLC) method which is capable for quantitatively estimation of Bilastine (BLS) and Montelukast (MTK) content present in dissolution media with accurately and precisely. A simple, fast, specific, rugged and reproducible analytical method was developed and validated on a Shimadzu HPLC equipped with diode-array detector. A Hypersil BDS C18-Column (100 mm x 4.6mm, 3µm) and 0.1%v/v Triethylamine buffer (pH-3.0):Acetonitrile used as mobile phase with flow rate 1.0 ml/min in gradient mode.The column oven temperature and sample cooler temperature was set to 40°C and 25°C respectively. Injection volume was10µL and chromatograms were recorded at 220nm. The optimized conditions for dissolution testing includes USP type-II apparatus at 75 rpm with 900mL, 0.5% w/v sodium lauryl sulphate media at 37.0 ± 0.5°C. Under above conditions the retention time of Bilastine and Montelukast was 7.23 and 1.84 min respectivelywithout any interference of dissolution media or any other degradant at the RT of both drugs. The calibration curve was found linear with R2 value 0.99987 and 0.99985 for BLS and MTK respectively and sample was found stable in dissolution media up to 12 hours. The analytical method was validated as per ICH guidelines with respect to specificity, precision, linearity, accuracy, stability in aqueous solution and robustness.The proposed method was found useful for the routine analysis of dissolution samples for quality control purposes.